Experimental analysis of separately controlled multi-coils on the performance of magnetorheological absorber under impact loading. (April 2016) - Zheng, Jiajia; Ouyang, Qing; Li, Zhaochun; Li, Yancheng; Wang, Jiong
A magnetorheological absorber is capable of actively adapting any gun recoil condition by means of controlled Coulomb force. The objective of multi-coil magnetorheological absorber with individual input currents is to mitigate the peak force transferred to the buffer structure during bullet firing, and thus to increase the structural fatigue life. This article investigates various cases by applying random combinations of input currents to the magnetic coils. The impact tests were conducted by obtaining and analyzing the force, displacement, and velocity. As a reference, input currents with equivalent magnitude are considered statistically, in terms of average peak force and occurrence time. The experimental results show that separately controlled multi-coils contribute to the magnitude and occurrence time of peak force significantly. Furthermore, to reduce peak forces, a simple open-loop control strategy was proposed and validated effectively by the experimental results.